Flourishing in subterranean ecosystems: Euro-Mediterranean Plusiocampinae and tachycampoids (Diplura, Campodeidae) - Sendra, Alberto; Antić, Dragan; Barranco, Pablo; Borko, Špela; Christian, Erhard; Delić, Teo; Fadrique, Floren; Faille, Arnaud; Galli, Loris; Gasparo, Fulvio; Georgiev, Dilian; Giachino, Pier Mauro; et al. (European Journal of Taxonomy, 2020)
Diplura is a group of entognathous hexapods, often considered a sister group to insects. They play an important role in recycling organic matter in soil and subterranean terrestrial ecosystems. The Campodeidae is the most diverse family, divided into four subfamilies. The subfamily Plusiocampinae has a subterranean life-style with many species distributed in the Euro-Mediterranean area. The incertae sedis tachycampoids (“lignée Tachycampoïde”) is a group within the family Campodeidae that share with the Plusiocampinae a strong preference for subterranean habitats and several morphological characters, such as slender body shape, elongated appendages, considerable increment in the number of antennomeres and cercal articles, and complexity of sensorial structures. The present monograph provides a taxonomic revision of the subfamily Plusiocampinae and the genera belonging to the tachycampoid lineage from Europe and the Mediterranean region. It comprises detailed morphological descriptions and illustrations together with data on the habitats and distributions of 87 species, 10 subspecies and 11 affinis forms. Seven new species are described among those, namely: Plusiocampa (Plusiocampa) apollo Sendra, Giachino & Vailati sp. nov., P. (P.) chiosensis Sendra & Gasparo sp. nov., P. (P.) dublanskii Sendra & Turbanov sp. nov., P. (P.) hoffmanni Sendra & Paragamian sp. nov., P. (P.) rhea Sendra sp. nov., P. (P.) ternovensis Sendra & Borko sp. nov. and P. (Venetocampa) ferrani Sendra & Delić sp. nov.